Nekatera odprta pravna vprašanja postopkov pri urejanju prostora in izdaji gradbenih dovoljenj - Gerbec, Franc (Podjetje in delo, 2016)
Process of spatial legal regulation, especially spatial planning and issue of building permits, always presents intervention into legally protected interests and rights of third parties, who are not investors or proposing spatial interventions. Such interventions by their nature introduce confrontation of different public interests, of public and private interests and also of different private interests. The article summarizes some key open legal issues and effectiveness of their coordination and assertion. It also deals with key %tools% or means of valid and of expected new related legal regulation. Effectiveness of coordination of different interests is perceived as neuralgic point of spatial planning and building permits procedures. By comparing regulations of such coordination mechanisms in some other countries, the author proposes introduction of similar mechanisms to new domestic legislation, e.g. establishment of Building council (working body of the Government of the Republic of Slovenia), establishment of expert working bodies with administrative units, issuing building permits. The author also proposes introduction of various out-of-court settlement procedures as more effective methods compared to legal procedures.
Keywords: gradbeno dovolojenje; pravna ureditev; prostorski razvoj; prostorsko planiranje; prostorsko urejanje; upravni postopek